Perjanjian Kerjasama Antar Pelaku Usaha Dengan Pihak Pemerintah Yang Penyelesaiannya Melalui Badan Arbitrase Nasional Indonesia (Bani) Medan (Studi Di Kota Medan) - Shah, Elbarino; Kamello, Tan; Andriati, Syarifah Lisa (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
This article aims to analyze the role of BANI Medan in resolving business settlements that occur between perpetrators and the government in Medan City. This research will also examine the factors that cause default in cooperation agreements as well as settlement efforts made by BANI Medan. Data was collected through document study, interviews with related parties, and direct observation of arbitration cases at BANI Medan and analyzed qualitatively. This study concludes that BANI Medan plays an important role in resolving business peace by providing efficient, fast and confidential arbitration. While there are challenges such as lack of awareness about arbitration, the benefits are clearly greater. With the increasing complexity of business in Medan, BANI's role is increasingly relevant. To prevent default in business agreements, it is important to draw up clear contracts, manage finances well, and understand the law. BANI Medan helps maintain a stable business environment and reduces sustainability risks.